2020
DOI: 10.1007/s42729-020-00192-3
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Accumulation and Nutritional Requirements of Potato as Affected by Potassium Supply

Abstract: Potassium (K) supply affects the growth and tuber yield of potato (Solanum tuberosum L.) as well as the uptake and removal of certain nutrients. However, information on this is scarce or inconsistent. Thus, this study was undertaken to evaluate the dry matter (DM) accumulation and the uptake and removal of nutrients by potato 'Agata' as affected by K fertilizer management (rates and application timings) in tropical clay soils with varied K availability. In soils with low K availability, K fertilization increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
2
5
0
1
Order By: Relevance
“…K fertilizer increased root, stem, and total plant N, P, and K accumulation and leaf N and K accumulation, and root and stem N, P, K content, and leaf N and P content. It showed that K fertilizer promoted root, stem, and leaf N, P, and K absorption and increased N, P, and K accumulation of P. bournei seedlings, consistent with some research results [17,47,48]. With the increase of K fertilizer rate, root, stem, and leaf N and P contents, and root, stem, leaf and total N, and P accumulation increased first and then decreased, indicating that excessive K fertilization may cause poisoning to the root system of P. bournei seedlings, reducing N and P absorption [49].…”
Section: Effect Of K Fertilizer On Nutrients Accumulation and Allocation In P Bournei Seedlingssupporting
confidence: 89%
“…K fertilizer increased root, stem, and total plant N, P, and K accumulation and leaf N and K accumulation, and root and stem N, P, K content, and leaf N and P content. It showed that K fertilizer promoted root, stem, and leaf N, P, and K absorption and increased N, P, and K accumulation of P. bournei seedlings, consistent with some research results [17,47,48]. With the increase of K fertilizer rate, root, stem, and leaf N and P contents, and root, stem, leaf and total N, and P accumulation increased first and then decreased, indicating that excessive K fertilization may cause poisoning to the root system of P. bournei seedlings, reducing N and P absorption [49].…”
Section: Effect Of K Fertilizer On Nutrients Accumulation and Allocation In P Bournei Seedlingssupporting
confidence: 89%
“…Omission of P has been found to affect the uptake of most of the essential plant nutrients on acidic to slightly acidic soils (Adalton Mazetti Fernandes et al, 2017;Borges et al, 2016;Kumar et al, 2018); this in turn affects most plant processes, thus reducing the yield. Higher uptake of N, K, Ca, Mg, S, B, Cu and Fe has been associated with P fertilization as a result of its effect on plant biomass (Fernandes et al, 2015;Fernandes et al, 2017;Soratto et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This would mean K needed in customised fertilizers is minimal. A recent study on tropical clay soil has shown that the benefits of K in improving uptake of other nutrients are reduced under medium and adequate levels of K in the soil (Soratto et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results of Abdel-Salam and Shams [15] were in the same line, highlighting the positive effect of combining various sources of potassium on potato plant growth, while Shunka et al [32] indicated the interaction of potassium application with other macronutrients such as nitrogen. Finally, Zelelew et al [33] reported a variable response to potassium fertilization depending on the potato cultivar, while Soratto et al [34] and Kumar et al [35] highlighted the importance of application timing and potassium source for crop response to potassium fertilization. In contrast, Ali et al [36] reported a positive effect on the growth of potato plants treated with feldspar-K and potassium-solubilizing bacteria; however, the results of that study are not comparable to the present work because different treatments were applied.…”
Section: The Effect Of Potassium Application On Plant Vegetative Grow...mentioning
confidence: 99%